EFFECT OF BRAIN GYM ON COGNITIVE FUNCTION IN ELDERLY WITH POST ISCHEMIC STROKE - Jumraini Tammasse; Sri Wahyun (Nusantara Medical Science Journal, 2016)
ABSTRACT  Introduction: This study to determine brain gym practice effect on cognitive function of elderly post ischemic stroke. Methods: This study was an experimental test conducted at Makassar, South Sulawesi from June 23rd, 2014 to December 16th, 2014. Thirty two subjects were divided into experimental and control groups in the same number. The brain gym movements will be performed in the experimental group. Control group did not perform the brain gym movements. The experimental group exercised twice a week for twelve weeks. Pre-test and post-test using The Consortium to Establish Registry of Alzheimer Diseases – Neurophysiological Battery (CERAD- NB) was performed to all subjects before and after twelve weeks intervention. The difference of CERAD-NB score between pre-test and post-test was analyzed using Mann Whitney U and Wilcoxon Sink Rank Test. Results: The study showed there was a significant improvement on cognitive function in experimental group and a significant decline of cognitive function in the control group. There was also significant difference in CERAD-NB score with Mann Whitney test (p<0,05) between the experimental group and the control group. Brain gym gives a positive effect on cognitive function in the elderly with post ischemic stroke.     Key words : Brain gym, cognitive function, elderly post ischemic strok